Performance comparison of different readouts for position-sensitive solid-state photomultiplier arrays. (19th July 2017) - Du, Junwei; Schmall, Jeffrey P; Di, Kun; Yang, Yongfeng; Dokhale, Purushottam A; Shah, Kanai S; Cherry, Simon R
Abstract: A thorough comparison of five different readouts for reading out a 2 × 2 array of 5 mm × 5 mm position-sensitive solid-state photomultipliers (PS-SSPM) was undertaken. The five readouts include reading out the 20 signals (16 position and 4 timing) individually, two signal multiplexing readouts, and two position decoding readouts. Flood histogram quality, signal-to-noise ratio (SNR) and energy resolution were compared at different bias voltage (27.0– 32.0 V, at 0.5 V intervals) and at a fixed temperature of 0 °C by coupling a 6 × 6 array of 1.3 mm × 1.3 mm × 20 mm polished LSO crystals to the center of the PS-SSPM array. The timing resolution was measured at a bias voltage of 31.0 V (optimal bias voltage in terms of flood histogram quality). The best flood histogram quality value and signal-to-noise were 7.3 ± 1.6 and 33.5 ± 3.1, respectively, and were obtained by shaping and digitizing the 16 position signals individually. The capacitive charge-division readout is the simplest readout among the five evaluated but still resulted in good performance with a flood histogram quality value of 3.3 ± 0.4 and a SNR of 18.3 ± 1.3. The average energy resolution and the average timing resolution were 15.2 ± 1.2% and 8.4 ± 1.6 ns for individual signal readout and 15.9 ± 1.2% and 8.8 ± 1.3 ns by using the capacitive charge-division readout method. These studies show that for an ultra-high spatial resolution applications using the 2 × 2 PS-SSPM array, reading out the 20 signals individually is necessary, whilst the capacitive charge-division readout is a cost-effective readout for less demanding applications.